Data Sheet 1_Self-assessed vs. reported digital competence among health students in Germany, Ukraine and Kazakhstan: a DigComp 2.2–based cross-sectional study.csv - Tom Schaal (4107358) (2025)
Introduction Digital competence is essential for students and professionals in health and nursing education. Based on the DigComp 2.2 framework, this study examines the self-assessed digital competencies of students from Germany, Ukraine, and Kazakhstan across five core dimensions, aiming to identify national differences and potential misalignments between perceived and reported digital competences. Methods A cross-sectional online survey (n = 269) was conducted among students in health-related fields. Participants rated their digital competence on 15 items aligned with DigKomp 2.2 questionnaire. Quantitative data were analyzed descriptively and with ANOVA (two-tailed, p < 0.05), using Games–Howell post-hoc tests in case of heterogeneity of variances and Kruskal–Wallis/Mann–Whitney tests as sensitivity analyses. In addition, an open-ended knowledge question asked respondents to describe their strategies for finding reliable online information. Responses were analyzed descriptively and qualitatively using inductive coding. Results While all groups reported generally high digital competence, German students rated themselves significantly lower in the Digital content creation dimension compared to their peers and the KaWuM reference sample. However, their responses to the open-ended question revealed methodologically advanced search strategies, including systematic literature reviews (n = 8), Boolean operators (n = 6), and use of AI tools (n = 1). Ukrainian students emphasized heuristic and comparative approaches, while Kazakhstani responses reflected pragmatic strategies under infrastructural constraints. Discussion The findings suggest a mismatch between self-assessed and actual digital competence, particularly among German students, who may underestimate their skills. This highlights the importance of triangulating quantitative self-reports with qualitative diagnostics. The study underscores the need for embedded digital skills training, especially in Digital content creation, across national contexts in health education.